Pancreatic Ductal Deletion of Hnf1b Disrupts Exocrine Homeostasis, Leads to Pancreatitis, and Facilitates TumorigenesisSummary - Evans Quilichini (Cellular and Molecular Gastroenterology and Hepatology, 2019)
Background & Aims: The exocrine pancreas consists of acinar cells that produce digestive enzymes transported to the intestine through a branched ductal epithelium. Chronic pancreatitis is characterized by progressive inflammation, fibrosis, and loss of acinar tissue. These changes of the exocrine tissue are risk factors for pancreatic cancer. The cause of chronic pancreatitis cannot be identified in one quarter of patients. Here, we investigated how duct dysfunction could contribute to pancreatitis development. Methods: The transcription factor Hnf1b, first expressed in pancreatic progenitors, is strictly restricted to ductal cells from late embryogenesis. We previously showed that Hnf1b is crucial for pancreas morphogenesis but its postnatal role still remains unelucidated. To investigate the role of pancreatic ducts in exocrine homeostasis, we inactivated the Hnf1b gene in vivo in mouse ductal cells. Results: We uncovered that postnatal Hnf1b inactivation in pancreatic ducts leads to chronic pancreatitis in adults. Hnf1bΔduct mutants show dilatation of ducts, loss of acinar cells, acinar-to-ductal metaplasia, and lipomatosis. We deciphered the early events involved, with down-regulation of cystic disease–associated genes, loss of primary cilia, up-regulation of signaling pathways, especially the Yap pathway, which is involved in acinar-to-ductal metaplasia. Remarkably, Hnf1bΔduct mutants developed pancreatic intraepithelial neoplasia and promote pancreatic intraepithelial neoplasia progression in concert with KRAS. We further showed that adult Hnf1b inactivation in pancreatic ducts is associated with impaired regeneration after injury, with persistent metaplasia and initiation of neoplasia. Conclusions: Loss of Hnf1b in ductal cells leads to chronic pancreatitis and neoplasia. This study shows that Hnf1b deficiency may contribute to diseases of the exocrine pancreas and gains further insight into the etiology of pancreatitis and tumorigenesis. Keywords: Pancreatitis, Pancreatic Cancer, Hnf1b, Ducts, Acinar-to-Ductal-Metaplasia